Methods of influence of the assessment of the competitiveness of the organization on the effective implementation of innovations - Volkodaeva A. V., Dunaev P. V. (Economics and management: realias and prospects, 2019)
Relevance of influence of competitiveness of the organization on effective introduction of innovations is proved. The process of introduction of an innovative product at the enterprise is considered.
Keywords: инновации; проект; project; innovation; innovation strategy; инновационный продукт; стратегия инновационной деятельности; конкурентоспособность организации; innovative product; competitiveness of the organization